UNGKAPAN KASAR DALAM MASYARAKAT MELAYU RAWA MEKAR JAYA KECAMATAN SUNGAI APIT KABUPATEN SIAK - Zelawati, Resna; Faizah AR, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to describe the form of rough expression of Malay society in Rawa Mekar Jaya Sungai Apit district Siak regency. The forms rough expression consists of a word, phrase and clause. The research was carried out by using qualitative research descriptive approach. The data source of this study from several informants of Malay society in Rawa Mekar Jaya Sungai Apit district Siak regency. The results of analysis was carried out that the form of rough expression was the form of words which divided into basic words as much as forty four data. The form of rough expression affixed as much seven data. The form of rough expression compound words as much as thirty seven data. Besides that, the form of rough expression phrases as much as nine data, and the form of rough expression clauses as much as ten data.Keywords: Rough expression, Malay society